Transnational Adoptions and Migration: Intersections and Challenges. The Slovenian Case - Sobočan, Ana M. (Two Homelands, 2011)
The paper addresses the topic of the situation of transnationally adopted children in their receiving country. Exploring the ways in which a person becomes a part of a national group and/or culture and drawing on research in the area of transnational adoptions and ethnicization, as well as possible coping strategies, I contend that there is much more to belonging than citizenship or legal kinship.